IDENTIFICATION OF COURT DECISIONS RELATED TO ONLINE ARISAN CASES IN INDONESIA FROM 2018-2024 - Ashila Xaviena Almira Molla; Mochammad Tanzil Multazam (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This research discusses the phenomenon of online rotating savings and credit associations (arisan) in Indonesia, which are becoming increasingly popular but also vulnerable to legal violations such as embezzlement and fraud. Method: Using the PRISMA method, this study identifies, screens, evaluates, and analyzes cases of online arisan from 2018 to 2024. Results: Based on data analysis from the Supreme Court Decisions, 249 cases related to online arisan were found, peaking in 2021. The study also explores the applicable legal framework, including the Electronic Information and Transactions Law (ITE Law) and the Civil Code (KUHPerdata), to understand the challenges and solutions in protecting arisan participants. The research results indicate that better legal awareness and regulation are needed to reduce the risk of violations in online arisan. Novelty: This research provides a systematic review of online arisan cases in Indonesia over a six-year period, combining legal case analysis with the PRISMA method to highlight trends, legal challenges, and the need for improved participant protection.